Stress and coping strategies among metabolic syndrome patients - Sakinah, Harith; Radziah, Mohd Fauzi (2015)
Increasing incidence of metabolic syndrome (MetS) becomes worldwide attention as it may affect not only physical health as general but also mental health. This study focused on the prevalence of stress among metabolic syndrome (MetS) patients and coping styles that have been used while dealing with the stress arise. Methods: A cross sectional study was conducted on patients with MetS attending Out Patient Clinic, Hospital Universiti Sains Malaysia. A total of 142 respondents (Males, n= 47; Females, n= 95) who fulfilled the selection criteria were interviewed using Malay version of questionnaires: Personal Stress Inventory (PSI) and Brief COPE. Data was analyzed using Statistical Package for the Social Sciences (SPSS 20). Results: Mean age for the respondent are 56.30 ± 11.66 years. The prevalence of stress among the respondents is 14.1% using ATP III definition. Malay ethnic (n = 133) was predominantly homogenous in this study. Female (13.4%), married (13.4%) and non- employed (12.0 %) respondents are having more stress. There are significant differences in coping styles like planning (p = 0.02), venting (p = 0.00), behavioral disengagement (p = 0.01) and self blame (p = 0.05). Acceptance (mean score, SD = 7.23, 1.19) and religion (mean score = 7.21, 1.20) are considered the most popular coping styles among the respondents. While the least used of coping style was substance abuse (mean score = 2.10, 0.87). However, there are no significant values between them.